The Effect of Democratic Autocratic and Laissez-Faire (Free) Leadership Style of Kindergarten Headmaster toward Teacher Discipline Performance at Kindergartens in Southeast Pontianak District - F. Puji Astuti; Aunnurahman Aunnurahman; Wahyudi Wahyudi (JETL (Journal of Education, Teaching and Learning), 2019)
A formal education institution achieving success one of the factors is the leadership style of the Headmaster. One that wants to be improved through leadership style is work discipline for teachers. This study has several objectives, namely (1) To determine the influence of democratic leadership style on the work discipline of kindergarten teachers in Southeast Pontianak Subdistrict; (2) To find out the influence of autocratic leadership style on the work discipline of Kindergarten teachers in Southeast Pontianak District; (3) To determine the effect of laissez-faire (free) leadership style on the work discipline of kindergarten teachers in Southeast Pontianak Sub-district; (4) Describe the simultaneous influence of leadership styles (democratic, autocratic, and laissez-faire (free)) TK headmasters on the work discipline of kindergarten teachers in Southeast Pontianak Sub-district. The research approach used in this study is a quantitative approach. The data source referred to in this study is the Headmaster of Kindergarten and Kindergarten teachers in the Southeast Pontianak Subdistrict of Pontianak City which amounts to a total of 83 people from 7 public and private kindergartens. In this study using a non-random sample is a purposive sampling method with a total sample of 34 teachers. The results showed that (1) the leadership style of the kindergarten headmasters in Southeast Pontianak sub-district varied, which can be seen from the results of the percentage of democratic leadership style of 39.8%, autocratic leadership style of 26.5%, and laizes-faire leadership style of 33, 7%; (2) The discipline of the performance of kindergarten teachers in the Southeast Pontianak sub-district has been good, which can be seen from the results of the percentage of discipline of teacher performance of 85.01% in the high / good category; (3) There is a significant influence between the leadership style of the Kindergarten Headmaster and the discipline of performance of Kindergarten teachers in the Southeast Pontianak District; (4) There is a significant influence between the democratic leadership style of the Headmaster of Kindergarten on the discipline of performance of Kindergarten teachers in Southeast Pontianak Sub-district; (5) There is a nonsignificant influence between the autocratic leadership style of the Headmaster of Kindergarten on the discipline of the performance of Kindergarten teachers in Southeast Pontianak District; (6) There is a nonsignificant influence between the autocratic leadership style of the headmaster of kindergarten on the discipline of performance of kindergarten teachers in the Southeast Pontianak sub-district.